MODEL TWO STAY TWO STRAY (TSTS) DALAM DISKUSI PADA PEMBELAJARAN BAHASA INDONESIA - Desy Rufaidah (CARAKA, 2015)
Through the speaking skill learning, the student learns how to speak in front of the public. One kind of the speaking skill is a discussion, inside of discussion student learning to present the opinion and receive the opinion from the other person along with the reason that can be responsible. However in discussion some of the student not quite active to follow the discussion. In this article, investigation discussion in learning the Indonesian Language with Two Stay Two Stray model (TSTS).